How to write about theatre - Fisher, Mark 1964- (Bloomsbury Methuen Drama, 2015)
"Today, more people than ever are writing about theatre, but whether you're blogging, tweeting or writing an academic essay, the challenges as a critic remain the same: how to capture a performance in words, how to express your opinions, and how to keep the reader entertained. This inspirational book shows you how to go about it and overcome these challenges."--Dust jacket.